PENGENDALIAN DALAM PEMANFAATAN LAHAN KAWASAN BANDUNG UTARA (STUDI PADA KECAMATAN CIDADAP KOTA BANDUNG) - Nia Pusparini (SOSIOHUMANITAS, 2020)
This research is motivated by the lack of optimal control over land use in the area of ​​North Bandung, Cidadap District, Bandung. This refers to the provisions of Bandung City Regulation No. 3 of 2006 which stipulates the North Bandung Area as a protected area and is supported by the Regional Regulation of West Java Province Number 2 of 2016, concerning Guidelines for the Control of Spatial Use in the North Bandung Region (KBU) as a Strategic Friend of West Java Province. Based on the background of the above problems, the researcher identified the problem as follows: How is control in the use of KBU land in Cidadap District? In solving the problem this research tries to apply the concept of Hasibuan, through ways of controlling, namely: Direct Control, Indirect Control, and Control Based on Exceptions (GR. Terry in Hasibuan, 2016: 246). Thus it is expected that through control methods can be applied to the KBU land use Cidadap District can run optimally. As for the research methods used qualitatively. Targeted outputs from the results of this study can be used as input and information about land use control in the North Bandung area of ​​Cidadap District so that it can be used as a model to be applied to the Cidadap District government in optimizing land use.